Reaction of Iron‐ and Tungsten Carbonyls with a Zwitterionic Fulvalene12. Issue 12 (8th September 2015) - Schmid, Dominic; Seyboldt, Alexander; Kunz, Doris
Abstract: The highly dipolar fulvalene1 reacts with pentacarbonyl iron(0) and hexacarbonyl tungsten(0) complexes under irradiation with UV light. The cyclopentadienyl complexes2 and3 formed are analysed by means of NMR and IR spectroscopy as well as X‐ray analysis. They are the first zwitterionic carbonyl complexes of fulvenes or fulvalenes. In the case of iron, the dinuclear complex2 consisting of a dicarbonyliron(+I)‐tetracarbonylferrat(–I) moiety is formed, whereas in the case of tungsten, the mononuclear tricarbonyl tungsten(0) complex3 is obtained. Abstract :